2010
DOI: 10.1186/1471-2407-10-350
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin H expression is increased in GIST with very-highrisk of malignancy

Abstract: BackgroundRisk estimation of gastrointestinal stromal tumours (GIST) is based on tumour size and mitotic rate according to the National Institutes of Health consensus classification. The indication for adjuvant treatment of patients with high risk GIST after R0 resection with small molecule inhibitors is still a controversial issue, since these patients represent a highly heterogeneous population. Therefore, additional prognostic indicators are needed. Here, we evaluated the prognostic value of cyclin H expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
5
15
0
Order By: Relevance
“…Along with the factors of large tumor size and high mitotic rate presented in the NIH consensus, several studies have defined other poor prognostic factors, Cyclin T1 such as epithelioid type, increased expression of cytoplasmic HuR and cyclin A, and a high Ki67 ratio (24)(25)(26)(27). Increased expression of cyclin H was also a poor prognostic factor in high-risk GIST patients (23). The present results showed that cyclin T1 may be another potential prognostic predictor for gastric GIST patients.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Along with the factors of large tumor size and high mitotic rate presented in the NIH consensus, several studies have defined other poor prognostic factors, Cyclin T1 such as epithelioid type, increased expression of cytoplasmic HuR and cyclin A, and a high Ki67 ratio (24)(25)(26)(27). Increased expression of cyclin H was also a poor prognostic factor in high-risk GIST patients (23). The present results showed that cyclin T1 may be another potential prognostic predictor for gastric GIST patients.…”
Section: Discussionsupporting
confidence: 65%
“…The expression of cyclins A, B, D and E appear to be associated with high-grade disease but not with the clinical outcome (20-22). In addition, cyclin H-positive patients have a poor prognosis when they have high-risk GIST and when they exhibit metastasis or recurrent disease (23). However, there are few effective clinical predictors for gastric GIST.…”
Section: Positive Cyclin T Expression As a Favorable Prognostic Factomentioning
confidence: 99%
“…Recent reports showed that cyclin H and p16 are indicators of high-risk GIST [24,25]. Most recently, Ihle et al [11] revealed that expression of cell-cycle regulators, such as cyclin D1, CDK4, p21, and p16, was associated with recurrence in 400 high-risk patients with GISTs.…”
Section: Discussionmentioning
confidence: 99%
“…89 Elevated cyclin H is associated with very high-risk gastrointestinal stromal tumors, and reduced or absent cyclin H expression correlates with lower proliferation in B-cell lymphoma. 90,91 The transcriptional regulation elicited by the CAK complex (cyclin H-CDK7-Mat1) impacts embryonic stem (ES) cell differentiation. The complex activates CDK1, CDK2, CDK4, and CDK6 through phosphorylation of the T-loop.…”
Section: Cyclins In the Regulation Of Stem Cellsmentioning
confidence: 99%